Lizzy: understanding attachment and loss in young people with complex needs - Edwina Grant; Mary McFarlane; Rita Crawford (Scottish Journal of Residential Child Care)
Lizzy is now a twenty year-old young woman with brown hair, lovely blue eyes and the most amazing smile. She has a great sense of humour and is a very sociable person. She enjoys going out and about, be it to the cinema, shopping trips, ten-pin bowling or for something to eat. When on form, she sparkles. She is an avid Dunfermline supporter attending all their home games with Richard, her foster father. One of the highlights of the year is Lizzy’s summer holiday which she really enjoys. She is absolutely passionate about desserts, especially anything chocolate flavoured. Lizzy enjoys being in company but also enjoys her own space. She knows her own mind.